Variações espaciais e temporais na abundância das espécies introduzidas em um hotspot de biodiversidade global, rio Iguaçu, Paraná, Brasil: impactos sobre a ictiofauna nativa - Daga, Vanessa Salete (2010)
The objective of this study was to evaluate the composition and structure of the assemblages of native and nonnative fish along the temporal and spatial gradient on the Iguaçu River, and their relations with environmental variables in five reservoirs. Samples were collected from January 2004 to December 2008, with periodicity quarterly in reservoirs Foz do Areia, Segredo and Salto Caxias, while in reservoirs Salto Santiago and Salto Osório samples were bimonthly. Catches were made with the aid of gillnets (mesh size of 2.4 to 16 cm) and trammel nets (witches, 6, 7 and 8 cm between non-adjacent), operated on the surface, margin and bottom, exposed for 24 hours with checked at 8:00, 16:00 and 22:00 hours. Fish caught were identified, measured and weighed. The community structure was evaluated by its attributes of species (richness), abundance (biomass and number of individuals) and diversity index of Shannon. The environmental variables were plotted on a matrix (physics and chemistry) and is summarized by principal component analysis (PCA). To summarize the data on the composition and structure of the assemblages of native and nonnative fish, analysis of non-metric multidimensional scaling (NMDS) was used. The degree of association between multivariate matrices (environmental variables and the composition and structure of the assemblages of native fish and non-native) was assessed by means of a Procrustes routine. During the study period were collected from 152,007 specimens, 148,084 individuals of native species and 3,923 specimens of non-native species, which were divided into six orders, 16 families, 32 genera and 50 species. The most abundant native species were Astyanax sp. B (40.1%), Astyanax sp. C (19.1%) and Pimelodus britskii (9.1%). The non-native species were more abundant Odontesthes bonariensis (85.1%), Prochilodus lineatus (7.5%) and Tilapia rendalli (4.9%). The distribution of abundance in numbers and weight was higher in Salto Santiago, both native and non native. Spatial and temporal differences were apparent for wealth, for both native and non native, but the Shannon diversity index showed significant differences only for native species. The composition and structure of the assembly of native and nonnative fish showed significant differences along the longitudinal gradient of the Iguaçu River. The physical and chemical variables (water temperature, water transparency, pH and electrical conductivity) were significant for the separation of the reservoirs along the longitudinal gradient. Procrustes analysis showed that an association exists between the physical and chemical variables, and the spatial arrangement of the composition and structure of the assemblages of native fish.